Inherently consistent temperature function for interaction parameters demonstrated for the Mg–Si assessment. (September 2016) - Liang, Song-Mao; Wang, Peisheng; Schmid-Fetzer, Rainer
Abstract: A new inherently consistent temperature function for interaction parameters, L, is proposed. It is designed for the unconstrained application of any optimization software, such as PanOptimizer or PARROT, to avoid artifacts, for example inverted liquid miscibility gaps or re-stabilization of liquid well below solidus. Without introducing additional system-dependent adjustable parameters, the new function automatically excludes both the exaggerated negative values of L at low temperature and the exaggerated positive values of L at high temperature. The viability of the new function is demonstrated by a complete Calphad re-assessment of the Mg–Si system, which is the prime example of the most challenging systems pertinent to both artifacts. For the first time the calculated Mg–Si phase diagram from 0 K to very high temperature is presented. The new assessment also includes the quantitative solidus data of (Si) and other previously not considered original experimental data. Graphical abstract: fx1 Highlights: A new inherently consistent temperature function for interaction parameters is proposed. The new function avoids artifacts both at high temperature and low temperature. Advantages are validated by Calphad assessment of the Mg–Si system. Calculated Mg–Si phase diagram from 0 K to very high temperature is presented.